PERANAN TEKNOLOGI SISTEM INFORMASI DAN PENERAPAN SAK ETAP DALAM PENGEMBANGAN MODEL LAPORAN POSISI KEUANGAN (Studi Kasus: BINA SISWA SMA PLUS CISARUA) - S Supriyati; Atep Darminta; Rio Yunanto (Labkat Press KA FTIK UNIKOM, 2012)
Bina Siswa SMA Plus Cisarua addressing in Jl. colonel canal masturi no. 64. At the time of document making, record-keeping of transaction relating to account real or financial position report account especially, Bina Siswa SMA Plus Cisarua has applied computer that is by using the application of Microsoft Office Word 2007 and Microsoft Excel 2007, in practice of control to relative financial position report account unable to be added with the duration process performed within financial statement making. For the problems then writer takes title: â€œThe Role Of Technology Information Systems And Aplication Of SAK ETAP On Development Model Financial Position Reportâ€. Research type which writer applies is research type academy, data type which writer applies is qualitative data and quantitative data, research design type which writer applies is research design deskriptif-analistis, research method which writer applies is descriptive research method, survey and eksperiment, data collecting technique which writer applies is field researcher what consisted of interview and observation library research, system development method which writer applies is methodologies orienting at process, data and output. System development structure applied is Iterasi. Design of information system applied is context diagram, data flow diagram, and flowchart. Design of this financial position report accounting information system according to statement of financial accounting standard SAK ETAP and output consisted of information of accumulated fixed assets, receivable list, transaction summary of cash, transaction summary of bank and financial position report.